СОВЕРШЕНСТВОВАНИЕ ПАРАМЕТРОВ СОВОКУПНОГО ФОНДА ПЕРИОДИКИ БИБЛИОТЕК НОВОСИБИРСКОГО НАУЧНОГО ЦЕНТРА СО РАН (Библиосфера, 2010)
The results of the research work and practice of serials collection forming in the Central Library of the Siberian Branch of the Russian Academy of Sciences are presented. The actual directions of development are revealed, the perspectives of libraries' interaction within the frames of the SB RAS in building the distributed collection of serials are outlined.